Manufacturing rationality the engineering foundations of the managerial revolution - Shenhav, Yehouda A. (Oxford University Press, 2011)
Management is a powerful mode of thought and code of conduct in the modern world, closely associated with the American way and a natural extension of economic progress. This book is about the history of management and the origin of managerial rationality.